KAJIAN POTENSI DAN STRATEGI PENGEMBANGAN EKOWISATA DI KAWASAN CAGAR ALAM PULAU SEMPU KABUPATEN MALANG PROVINSI JAWA TIMUR - , Tatag Muttaqin, Dr. Ir. Ris Hadi Purwanto, M.Agr. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Sempu Island which is located in the south of the island of Java was set as a Natural Preserve by decree of the governor general of the Dutch East Indies government in 1928. The access into this area is through ecotourism of Sendang Biru Beach and thus forming an opinion that Sempu Island Natural Preserve is one package tour with Sendang Biru Beach. The research was conducted in Sempu Island Natural Preserve Malang District East Java Province from April 2011 to March 2012. The purpose of this study was to examine the condition of Sempu Island Natural Preserve, to access its tourism potential, and to investigate the appropriate strategies for the development of ecotourism in the area of Sempu Island Natural Preserve. The study was conducted by survey method